Motivation to enter the police profession in the post-Ferguson era: an exploratory analysis of procedural justice - Morrow, Weston J. (Criminal justice studies, 2021)
The process-based model of regulation has become a dominant framework for understanding why people obey the law. Grounded in past and present research, the current study explores how the process-based model of regulation may explain motivational differences for entering the police profession in the post-Ferguson time era: a time period in which police agencies are expressing increased difficulties recruiting and hiring new officers. Some commentators have attributed these challenges to the heightened levels of public and media scrutiny. Considering the hiring challenges faced by law enforcement agencies, the current study investigates whether students’ (i.e. prospective police officers) motivation to enter the police profession is influenced by the procedurally just treatment of individuals by the police. Using a sample of college students from two universities, the findings provide support for the aforementioned inquiry. The implications of these findings are contextualized against the backdrop of the Ferguson Effect, procedural justice, and hiring challenges in the police profession.